DESKRIPSI LANGKAH-LANGKAH MODEL KOOPERATIF DALAM RPP TEMATIK KELAS III SEKOLAH DASAR - Asriati Pindarti Ningsih; Tahmid Sabri; Siti Halidjah (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe the steps of the cooperative model in the implementation plan of the third grade thematic learning at State Elementary School 02 Rasau Jaya. The research method used in this research is descriptive qualitative research method. With the form of case study research. Sources of data in this study were third grade teachers at State Elementary School 02 Rasau Jaya and 3 lesson plans. Data collection techniques in this study are interview techniques, observation techniques, documentation techniques, triangulation techniques. In this study, the researcher acted as the main instrument and the interview was used as a supporting instrument. The analysis technique in this study uses four steps, namely data collection (data collection, data reduction), data presentation, and the process of drawing conclusions. The results show that the teacher has not displayed the six steps of the cooperative learning model completely. groups, conduct learning evaluations as the final assessment in the learning process and provide rewards if students get good results.Keywords: cooperative learning, learning implementation plans, thematic.